The control of cellular adhesion of Saccharomyces cerevisiae by the FLO gene regulator Mss11p - Bester, Michael Christiaan (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Science) (Viticulture and Oenology. Wine Biotechnology))--University of Stellenbosch, 2010.